Training the physical trainer in young Moroccan football players to access the professional contract - (:unkn) unknown (My University, 2018)
Football is in constant development, detection, the development of young talents have become strategic and economic priorities for clubs and federations. The structures offering afootball training for the child are developing and are becoming more numerous: sports studiessections, pre-training centers, training centers and academies allow young people to pursue their passion and / or their dream high level. Nevertheless, it is important to remember that the development of the young can not be assimilated to that of the adult and the professional player: "The child is a little man and not a little man" (Jean Jacques Rousseau). The content of the training must respect principles adapted to their age and level. But what content ? The main aim of this thesis is to determine the impact of six years of physical training in the technical-tactical strategy on young football players in training to reach the highest level. Toprovide a complete literature review on all indicators of the performance and speed of the football player in training, as well as on the various influencing factors. In a second step, the objective of this thesis is to study the influence of a training program of two types of work of speed and to analyze their impact on the speed of starting and the first meters (0 to 10 meters) applied to Moroccan football players aged 12-17 (STUDY 1). Then we analyzed the impact of the different evolutionary stages of physical qualities and performances on technical and tactical skills in the performance of football (STUDY 2). STUDY 3 examined how performance improves among young Moroccan elite footballers in six football seasons (12-17 years) related to changes in anthropometric characteristics and physical qualities. The results of this third study have established, for the first time in Africa: the profile of the young 17-year-old North African football player (U18). Finally, in addition, a clinical study (STUDY 4), during six seasons of training prefo
Keywords: African Research